Landscapes protected by the forest code and by SNUC: analisis of functions, composition, and configuration - Sousa, Ana Caroline Rodrigues Cassiano de (2021)
The composition and configuration of landscapes can be indicators of anthropic pressures. Therefore, this article aims to characterize the main landscapes which are protected by Brazilian Forest Code and by the Nacional System of Conservation Units, identifying what are the influences of its structure in their legal function. From the comparative analysis between the laws, it was found that from the eleven groups of protected areas, the main functions are protectionist and anthropic; the majority of them are made of little patches – with greater influences of fragmentation – or big patches with low restrictions of use; and connectivity among fragments is incentivized only as recommendation, not as an exigency.